Good Governance Dalam Pelayanan Publik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bone - Selviani Arifin (Departemen Ilmu Pemerintahan Fisip Unhas, 2025)
Quality public service is one of the primary indicators of the successful implementation of good governance principles in public administration. The Department of Population and Civil Registration of Bone Regency, as the institution responsible for population administration services, is required to provide effective and efficient services to the public. However, various issues remain, including delays in document processing, inadequate facilities and infrastructure, and public complaints regarding service procedures that are considered less than optimal. This study aims to analyze the implementation of good governance principles in public service delivery at the Department of Population and Civil Registration of Bone Regency, particularly from the perspectives of effectiveness and efficiency. This study employed a qualitative descriptive research method. Data were collected through observation, interviews, documentation, and literature review. The data were analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of good governance principles in population administration services at the Department of Population and Civil Registration of Bone Regency has not yet been fully optimized. In terms of effectiveness, there are still residents who have not completed electronic identity card registration and do not possess birth certificates, while complaints regarding service quality and supporting facilities remain evident. In terms of efficiency, service requirements are still perceived as relatively complicated by some members of the public. Furthermore, service procedures, document processing time, and the availability of facilities and infrastructure require further improvement to enhance the quality of public services. Nevertheless, service fees are provided free of charge, and service officers generally demonstrate adequate competence in serving the community.